PENGARUH GAYA HIDUP HEDONISME, MATERIALISME DAN PENDAPATAN TERHADAP SHOPPING LIFESYLE SERTA DAMPAKNYA PADA PEMBELIAN IMPULSIF ONLINE PRODUK FASHION PADA MASYARAKAT KOTA BANDA ACEH - Aidil Syahputra; Mukhlis Yunus; Mahdani Ibrahim (Jurnal Manajemen Inovasi, 2017)
ABSTRACTThe purpose of the study was to determine: (1) the condition of Hedonism Lifestyle, Materialism, and Income toward Shopping Lifestyle and its impact on Impulsive Buying online fashion product in The Society of Banda Aceh; (2) the effect of Hedonism Lifestyle, Materialsm, Income and its impact on Impulsive Buying online fashion product in the Society of Banda Aceh; (3) the effect of shopping lifesyle and its impact on Impulsive Buying online fashion product in the Society of Banda Aceh; (4) the effect of Hedonism Lifestyle, Materialsm, and Income indirectly toward Impulsive Buying online fashion product in the Society of Banda Aceh Through Shopping Lifestyle. The sample of the study was 100 responden which were selected by the purposive sampling technique, and analysed using path analysis. The result showed that  Hedonism Lifestyle, Materialism, and Income have a positive influence on Shopping Lifestyle as well as online impulsive buying on fashion products. The results of the research on Shopping Lifestyle showed an influence on the improvement of online Impulsive buying on fashion products. The results also indicate that there is indirect influence between Hedonism Lifestyle, Materialism and Income to impulsive Buying Online fashion product in Banda Aceh society through Shopping Lifestyle.Keywords :     Hedonism Lifestyle, Materialism, Income, Shopping Lifestyle, Impulsive   Buying